Analysis of Innovation Trends in Mathematics Learning Models in Improving Students' Critical Thinking Skills: A Systematic Literature Review - 'Afifah, Nur (Lembaga Riset Mutiara Akbar, 2025)
Critical thinking skills are an essential competency in 21st-century mathematics learning. This study aims to analyze trends in innovation in mathematics learning models that contribute to the development of students' critical thinking skills through a systematic literature review approach. Articles were collected from various scientific databases such as Google Scholar, ERIC, ScienceDirect, and accredited national journals, with inclusion criteria being publications from 2015–2025, full access, and relevance to the topic. Of the 15 selected articles, it was found that learning models such as Problem-Based Learning (PBL), Realistic Mathematics Education (RME), Project-Based Learning (PjBL), STEM-based learning, and digital media integration such as Wordwall are the dominant approaches that have proven effective. These models are able to develop critical thinking dimensions such as analysis, evaluation, reflection, and problem-solving. However, challenges in implementation such as teacher readiness and limited resources remain major obstacles. This study recommends strengthening teacher training and policy support as strategic steps in encouraging the adoption of innovative learning models that have an impact on improving the quality of students' critical thinking.